2018
DOI: 10.1021/acssuschemeng.8b02049
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Yellow Pigments of Bi1.7RE0.3W0.7Mo0.3O6 (RE = Y, Yb, Gd, Lu) with High NIR Reflectance

Abstract: Brilliant yellow-orange pigments based on the formula Bi1.7RE0.3W0.7Mo0.3O6 (RE = Y, Yb, Gd, Lu) are developed by the traditional solid-state reaction method. Relevant techniques are used for characterization of the crystal structure, morphology feature, reflectance property, and color performance of the prepared pigment. The doping of RE/Mo in Bi2WO6 results in the colors of pigments varying from faint yellow to brilliant yellow-orange. Compared with Bi2WO6 pigment, the typical pigment of Bi1.7Lu0.3W0.7Mo0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Many studies have been reported on several colored pigments that can reect NIR light. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The NIR-reectance properties of variously colored pigments (e.g. white, yellow, and blue) are generally better than those of black pigments, because these pigments tend to reect not only visible but also NIR light.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on several colored pigments that can reect NIR light. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The NIR-reectance properties of variously colored pigments (e.g. white, yellow, and blue) are generally better than those of black pigments, because these pigments tend to reect not only visible but also NIR light.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the separation and transfer of photoinduced charges are highly facilitated, consequently giving rise to the improved photocatalytic activities. [115] Another typical bismuth-based p-n junction is BiOX/g-C 3 N 4 heterojunction. [116117] Many pentavalent bismuthates exhibit excellent visible-light driven photocatalytic performances.…”
Section: Pàn Junctionsmentioning
confidence: 99%
“…[159] This prominent enhancement of photocatalytic performance and efficient separation of photoinduced electron-hole pairs are attributed to the construction of a Z-scheme structure and reliable interfacial interaction of BiVO 4 /g-C 3 N 4 . A series of techniques, [115] nÀBi 12 O 17 Cl 2 / pÀBiOI photocatalytic oxidation of 2,4-DCP, RhB, phenol, BPA, and tetracycline hydrochloride [119] nÀSr 2 TiO 4 / pÀBi 5 O 7 I photocatalytic oxidation of MO [120] pÀBiOI/ nÀBiPO 4 photocatalytic oxidation of MO and phenol [121] pÀBiOBr/ nÀLa 2 Ti 2 O 7 photocatalytic oxidation of RhB and phenol [122] pÀBiOI/ nÀBi 2 O 2 CO 3 photocatalytic oxidation of RhB [123] pÀBiOI/ nÀgÀC 3 N 4 photocatalytic oxidation of BPA [124] nÀBiPO 4 / pÀBiOBr Photocatalytic activity for formaldehyde Oxidation; photocatalytic oxidation of RhB [125126] pÀBiOCl/ nÀBiVO 4 photocatalytic oxidation of RhB [127] pÀBiOI/ nÀBiOIO 3 photocatalytic oxidation of MB [30] pÀCuBi 2 O 4 / nÀBiWO 6 photocatalytic oxidation of MB and photocatalytic reduction of Cr 2 O 7 2À [128] pÀBiOCl/ nÀBiVO 4 photocatalytic oxidation of MO [129] pÀBi 2 O 3 / nÀBi 2 WO 6-x F 2x photocatalytic oxidation of RhB [130] pÀBiOCl/ nÀBi 2 O 2 CO 3 photocatalytic oxidation of RhB [131] pÀBi 2 O 3 / nÀBi 2 WO 6 photocatalytic oxidation of RhB and phenol [114] pÀBiOI/ nÀMnNb 2 O 6 degradation of antibiotics (TC, oxytetracycline, ciprofloxacin and doxycycline) [132] pÀBiOBr/ nÀCeO 2 photocatalytic oxidation of RhB, MB and phenol [133] pÀBiOBr/ nÀBi(C 2 O 4 ) OH photocatalytic oxidation of RhB [134] pÀBi 2 O 3 / nÀBi 2 MoO 6 photocatalytic oxidation of RhB and 2,4-DNP [135] pÀBiOBr/ nÀZnO photocatalytic oxidation of phenol [136] pÀBiOBr/ nÀBiOIO 3 photocatalytic oxidation of RhB, MB, MO and crystal violet [137] pÀBiOBr/ nÀTiO 2 photocatalytic oxidation of RhB and photocatalytic H 2 generation [138] pÀBiOI/ nÀBrÀBi 2 O 2 CO 3 photocatalytic oxidation of MO [139] pÀBiOI/ nÀBi 2 Sn 2 O 7 photocatalytic oxidation of RhB [140] pÀBiOI/ nÀSnS 2 photocatalytic oxidation of RhB [141] nÀFe 2 O 3 / pÀBiOI photocatalytic oxidation of RhB…”
Section: Z-scheme Heterojunctionsmentioning
confidence: 99%
“…To the best of our knowledge, heat build-up in the environment is mainly due to radiation of sunlight in the near-infrared band (750–2500 nm), especially in extremely hot weather . The use of high near-infrared reflective materials helps in maintaining the material surface at a lower temperature, minimizing the human bodyʼs absorption of solar thermal energy, and improving the thermal comfort of urban living . Recently, plenty of inorganic pigments, such as Mo-doped Bi 2 WO 6 , Tb-doped A 2 CeO 4 (A = Sr and Ba), Cr-doped BaTiO 3 , and BiVO 4 –ZnO, have been reported as near-infrared reflective pigments. However, most near-infrared reflective pigments are used as cold coatings in the construction industry but rarely on fabric surfaces .…”
Section: Introductionmentioning
confidence: 99%